Evaluation of 6, 8-Dichloro-2-Methyl-4H-Chromen-4-One Derivatives as Antileishmanial Agents (Global Journal of Science Frontier Research, 2012)
The present work aims at study of antileishmanial activity of some 6, 8-dichloro-2methyl-4H-chromen-4-one derivatives. The synthesized chromenes have been screened for antileishmanial activity on L. major parasite. The results were promising and showed that all compounds under investigation have some degree of activity against leishmania L. major parasite and compound 5 showed potential activity with IC 50 value 0.58± 0.09 μg/ml, comparatively with the standard drug Amphotericin B.
Keywords: 2-methyl-4h-chromen-4-one; carbon electrophiles and nucleophiles; leishmaniasis